The Effect of A2E on the Ca2+-PKC Signaling Pathway in Human RPE Cells Exposed to Blue Light - Maomei Luo; Shu Wang; Yun Tang; Chun Zeng; Shanjun Cai (Journal of Ophthalmology)
Aims. In a model of blue light-induced damage in N-retinylidene-N-retinylethanolamine (A2E)-loaded human retinal pigment epithelial (RPE) cells, we examined the effect of A2E on the calcium (Ca2+)-protein kinase C (PKC) signaling pathway. Methods. Primary human RPE cells were cultured, and the cells in the 4th–6th passages were used in this study. The cells were divided into 5 groups: control cells (no A2E, no blue light), blue light-treated cells, blue light + chloroquine-treated cells, blue light + A2E-treated cells, and blue light + A2E + chloroquine-treated cells. The cells were first treated with chloroquine (15 μM for 12 h) and then loaded with A2E (25 μM for 2 h).The blue light intensity was 2000 ± 500 lux, and the duration was 6 h. After blue light exposure, the cells were cultured for 24 h. Fluo-3/AM staining was used to determine the level of cytoplasmic Ca2+, and the cells were photographed using a laser scanning confocal microscope to analyze the fluorescence intensity. The intracellular levels of inositol triphosphate (IP3) and diacylglycerol (DAG) were measured by enzyme-linked immunosorbent assay (ELISA). Intracellular PKC activity was measured with a nonradioactive nuclide assay. Results. Among all cell groups, the levels of Ca2+, DAG, and IP3 were lowest in the control cells (P<0.05). The Ca2+, DAG, and IP3 levels in the blue light + A2E-treated cells and blue light + chloroquine-treated cells were higher than those in the blue light-treated cells (P<0.05). The Ca2+, DAG, and IP3 levels were highest in the blue light + A2E + chloroquine-treated group (P<0.05). PKC activity was lowest in the control cells (P<0.05). The PKC activity of the blue light + A2E-treated cells and blue light + chloroquine-treated cells was higher than that of the blue light-treated cells (P<0.05), and the PKC activity of the blue light + A2E + chloroquine-treated cells was the highest (P<0.05). Conclusion. Blue light and A2E increased the levels of Ca2+, IP3, and DAG in human RPE cells and enhanced PKC activity, and blue light and A2E had a synergistic effect. Chloroquine further increased the levels of Ca2+, IP3, and DAG and PKC activity in RPE cells or A2E-loaded RPE cells exposed to blue light.